On the Gauss map of a class of hypersurfaces in ℍ4 - Turgay, Nurettin Cenk; Güler, Erhan (Author(s), 2018)
We consider hypersurfaces of Riemannian space forms in terms of the type of their Gauss map, spherical Gauss mapor hyperbolic Gauss map. We give a brief summary of results on submanifolds withLkfinite type Gauss map fork>0. We alsoobtain some classification results.